STRUKTUR LEGITIMASI DALAM MASYARAKAT INDONESIA (Studi Pengukuhan Kembali Kerajaan Gunung Sahilan Kabupaten Kampar Provinsi Riau) - Mulianto, Budi; Fikri, Rijalul (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2018)
Democratization in Indonesia provides an opportunity for the community to maintain and preserve the values, norms and beliefs of ancestors that are manifested in the cultural traditions and customs. Then to strengthen the tradition makes the existence of traditional institutions as a form of legitimacy and community identity. The existence of the Gunung Sahilan Kingdom that has experienced a leadership vacuum for a long time, raises questions, approximating what then makes Raja Gunung Sahilan re-established in the Gunung Sahilan Kingdom, traditional authority can be clearly seen from the royal structure that can be said to be not elite centric. The Kingdom of Mount Sahilan adopted a system of functional assignment within its government. The kingdom in the Kingdom of Gunung Sahilan as a symbol and symbol of the greatness of the institution. In the structure of the Kingdom of Gunung Sahilan Raja itself as the highest government that controls custom (government) and worship. Sahilan is "Tengku Yang Dipertuan Besar" and for the King of Worship "Tengku Yang Dipertuan Sati". Government affairs in the sense that the executive is controlled by an institution called the Khalifah Density which has four homecoming with Dt. The great Caliph Van Kampar left. The position of these caliphs in the Kingdom of Gunung Sahilan is as a Ministerial Assembly (Ministry) where the function is divided according to certain parts. The rise of the Kingdom of Gunung Sahilan has become a basis for legitimacy to preserve and preserve traditional values by re-integrating the density of adat throughout the Kampar Kiri. Later, by re-existing the Gunung Sahilan Kingdom is inseparable from the legitimacy structure that is already formed and takes root in authority traditional authority. The existence of this traditional institution is a reinforcement of the community structure within the framework of the democratization of the Republic of Indonesia, because in addition to its existence as a local identity that is maintained, it is also a special feature for democracy in Indonesia.